Caspase Inhibitor Diminishes Caffeic Acid-induced Apoptosis in Osteosarcoma Cells - Ferry Sandra; Karina Febriani Hudono; Amelia Astriani Putri; Chantika Amardhia Paramita Putri (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Caffeic acid has been shown to induce apoptosis in MG63 osteosarcoma cells. Along with the apoptotic induction, caffeic acid was shown to activate caspase-8, -9 and -3. However, the role of caspase in mediating caffeic acid-induced apoptosis in MG63 cells are not clear yet. In this study, caspase role was further investigated by inhibiting caspase activity in the caffeic acid-induced apoptosis system in the MG63 cells.METHODS: MG63 cells were cultured, starved, pretreated with/without Z-VAD FMK and treated with/without 10 µg/mL caffeic acid. To quantify the number of apoptotic MG63 cells, Sub-G1 method was performed. The caffeic acid-induced apoptotic morphology was confirmed with 4',6-diamidino-2-phenylindole (DAPI) staining and Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Meanwhile, to detect apoptotic underlying mechanism, immunoblotting was performed to detect caspase-8, -9 and -3.RESULTS: MG63 cells were significantly induced into apoptosis with the treatment of 10 µg/mL caffeic acid for 48 hours. However, pretreatment of 100 µM Z-VAD-FMK, a pan caspase inhibitor, for 2 hours, the percentage of apoptotic MG63 cells was significantly diminished. The apoptotic phenomenon induced by caffeic acid as well as the inhibition of Z-VAD-FMK were confirmed by DAPI staining and TUNEL assay. Cleaved caspase-8, -9 and -3 were formed markedly upon the treatment of caffeic acid. Pretreatment of 100 µM Z-VAD-FMK could inhibit the cleaved caspase-8, -9 and -3.CONCLUSION: Taken together, caffeic acid has the potential to induce apoptosis in MG63 cells, specifically through the caspase signaling pathway.KEYWORDS: caffeic acid, apoptosis, MG63, caspase, Z-VAD FMK